Individual Variability in Recognition of Frequency-Lowered Speech - Alexander, Joshua M. (Seminars in Hearing, 2013)
Frequency lowering in hearing aids is not a new concept, but modern advances in technology have allowed it to be performed more efficiently and on select portions of the spectrum. Nonlinear frequency compression reduces the frequency spacing in a band of high-frequency energy so that more information is carried in the audible bandwidth. Frequency transposition and translation techniques lower only the part of the high-frequency spectrum that likely contains important speech information. These advances may help overcome the limited bandwidth in conventional hearing aids, which restrict access to high-frequency information even for those with mild to moderate hearing loss. This is especially important for young children learning speech and language. A framework is advanced in which factors that influence individual differences in speech recognition can be divided into extrinsic factors that affect the representation of the frequency-lowered speech at the auditory periphery, including the specific technique and the settings chosen for it, and intrinsic factors that contribute to an individual's ability to learn and benefit from this signal. Finally, the importance of electroacoustically verifying the output to avoid too little or too much lowering and the importance of validating effectiveness of outcomes in individual users of the technology are emphasized.
Keywords: Hearing aids; frequency lowering; frequency compression; frequency transposition